Avifauna of the Estação Ecológica do Rio Acre, state of Acre, on the Brazil/Peru border: composition, ecological distribution, and noteworthy records - Aleixo, Alexandre; Guilherme, Edson (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
We carried out an ornithological inventory at the Estação Ecológica do Rio Acre (ESEC Rio Acre), a remote conservation unit in southern Acre, on the Brazil/Peru border, to contribute data for the unit’s management plan. Surveys took place during two separate expeditions in the dry (August 2005) and the wet season (February 2006), and included qualitative (observations, tape-recording) as well as quantitative (mist-netting) sampling techniques. We accumulated 180 hours of qualitative observations and ca. 2,500 mist-net.hours during 26 days, recording 365 species of birds. Several noteworthy records are discussed in detail here due to their relevance for Amazonian biogeography and conservation. The general results obtained, including the observation of large populations of bird species that are highly valued for hunting, indicate that ESEC Rio Acre is still very well preserved. Unfortunately, this can easily change if logging, which is currently taking place on the Peruvian side of the border adjacent to ESEC Rio Acre, crosses the border illegally into Brazil.